PENGEMBANGAN MODUL DENGAN MODEL POE2WE (PREDICTION, OBSERVATION, EXPLANATION, ELABORATION, WRITE, DAN EVALUATION) DALAM MENINGKATKAN KOMPETENSI MAHASISWA - Vepi Apiati; Siska Ryane Muslim (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Learning modules are learning materials that can be studied by students independently, in which there are clear components and instructions so that students can follow them sequentially without the intervention of the teacher. Module Development with the POE2WE Model using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The Analysis stage includes analysis of performance, students, concepts, and objectives, the Design stage includes the preparation of modules according to the syllabus and lesson plan, and designing learning scenarios, the Development stage includes development with suggestions and input from material expert validators and the POE2WE model, the Implementation stage includes implementing the Module for 6th semester students, and the Evaluation stage includes an assessment of all stages from Analysis to Implementation. The learning model used is the POE2WE model (Prediction, Observation, Explanation, Elaboration, Write, Evaluation). The Prediction stage students make predictions, the Observation stage students make temporary conjectures, the Explanation stage students clarify their conjectures, the Elaboration stage students look for interrelationships of problems with everyday life. In the Write stage, students record the results of discussions and draw conclusions, and in the Evaluation stage, students answer questions for process assessment. This can increase the competence of students